Underlying beneficial effects of Rhubarb on constipation-induced inflammation, disorder of gut microbiome and metabolism - Gao, Han; He, Chengwei; Hua, Rongxuan; Liang, Chen; Wang, Boya; Du, Yixuan; Xin, Shuzi; Guo, Yuexin; Gao, Lei; Zhang, Lucia; Shang, Hongwei; Xu, Jingdong (Frontiers in Pharmacology, 2022)
Background: Constipation is a common syndrome and a worldwide healthy problem. Constipation patients are becoming younger, with a 29.6% overall prevalence in children, which has captured significant attention because of its epigenetic rejuvenation and recurrent episodes. Despite the usage of rhubarb extract to relieve constipation, novel targets and genes implicated in target-relevant pathways with remarkable functionalities should still be sought for. Materials and methods: We established a reliable constipation model in C57B/6N male mice using intragastric administration diphenoxylate, and the eligible subjects received 600mg/25g rhubarb extract to alleviate constipation. Resultant constipation was morphological and genetically compared with the specimen from different groups. Results: Constipation mice exhibited thicker muscle layers, higher levels of cytokines, including IL-17 and IL-23, and lower content of IL-22. Bacterial abundance and diversity varied tremendously. Notably, the alterations were reversed following rhubarb extract treatment. Additionally, Constipation also had a substantial impact on short-chain fatty acids (SCFAs), medium- and long-chain fatty acids (MLCFAs), and the expression of SCFA receptors, GPR41 and GPR43. Conclusion: This thesis has provided insight that rhubarb extract promoted the flexibility of collagen fiber, reduced pro-inflammatory cytokines, enhanced anti-inflammatory cytokines, and maintained gut microflora balance with potential impacts on the fatty acid and polyamine metabolism.